A Neutrosophic Model for Assessing the Impact of Artificial Intelligence on Civil Liability - María Gracia Paredes-Morales; Gino Joel Alberdy-Rodriguez; Susy Grey Morales-Cobos; Dessire Amandiz Castro-Valderrama; Gloria Angélica Valderrama-Barragán; Edwin Favio Valderrama-Barragán (Neutrosophic Sets and Systems)
The creation of Artificial Intelligence (AI) tools has grown exponentially in recent years. The number of these tools, their capabilities to solve problems and the number of people who use them are increasing rapidly. This constitutes a positive advance for humanity; however, there is also a negative side that can arise from its inappropriate use. To avoid the problems that may arise with the improper use of AI, it is necessary to have a regulatory legal framework that offers the guidelines to follow for evaluating the AI tools that arise and the civil and criminal consequences for those who fail to comply with what is established. This is an extremely complex problem since AI is constantly changing at a faster pace than lawyers understand the subject and the changes in the laws that must be applied. In our case, Ecuadorian legislation is not sufficiently prepared to face the problem, there is indeterminacy that manifests itself in the legal loopholes where some individuals can get away with it or be unfairly convicted. This paper proposes a model to help calculate the impact of AI on civil liability, especially in the legal system. Neutrosophic logic and other tools from this discipline are specifically used because they allow the explicit representation and calculation of the indeterminacy that is part of this problem that occurs in real life.